THE DIALECTIC OF RELIGION AND LOCAL CULTURE IN THE PRACTICE OF CULTURAL PROPAGATION - Putra Muallimin (Yayasan An-Nur Meunara Baro, 2025)
This study examines the dialectical process between Islamic teachings and local culture within the practice of dakwah kultural (cultural propagation) in Indonesia. Employing a qualitative case study approach with ethnographic methods, the research analyzes how this interaction unfolds not as a simple accommodation, but as a dynamic field of negotiation, strategic reinterpretation, and hybrid synthesis. The findings reveal a three-stage, non-linear cycle: strategic adaptation of religious messages into cultural frameworks, contested negotiation often involving tension with puritanical perspectives, and the emergence of contextual syntheses that create locally-grounded,